2010
DOI: 10.1007/s00586-010-1665-6
|View full text |Cite
|
Sign up to set email alerts
|

A modified “far-lateral” approach for safe resection of retroodontoid dural cysts

Abstract: Cystic mass lesions at the ventral craniocervical junction have been described only rarely in the past, however, they have received more attention with improved imaging modalities in recent years. These lesions have been approached by various operative procedures. A modified ''far-lateral'' approach combined with a C1 hemilaminectomy without fusion was used to safely remove the cyst and decompress the cervical medulla in a 72-year-old woman with cervicooccipital pain and paresthesia in both arms. Following sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Bertalanffy et al 13 utilized a long paramedian incision and muscle-splitting approach in one of the first reports describing a far-lateral transcondylar modification to suboccipital craniotomy. More recently, Lutjens et al 14 reported a modified far-lateral approach using a paramedian muscle-splitting approach for resection of a retro-odontoid dural cyst. Here we present an anatomical and clinical study that demonstrates the feasibility of the minimal access far-lateral approach in treating a variety of foramen magnum lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Bertalanffy et al 13 utilized a long paramedian incision and muscle-splitting approach in one of the first reports describing a far-lateral transcondylar modification to suboccipital craniotomy. More recently, Lutjens et al 14 reported a modified far-lateral approach using a paramedian muscle-splitting approach for resection of a retro-odontoid dural cyst. Here we present an anatomical and clinical study that demonstrates the feasibility of the minimal access far-lateral approach in treating a variety of foramen magnum lesions.…”
Section: Introductionmentioning
confidence: 99%